Psychometric validation and cultural adaptation of the Chinese version of the CarerQol-7D instrument - Richard Huan Xu; Yuanshuo Xu; Mengping Zhao; Nan Liu; Pei Wang; Xiao Liang; Lingming Zhou (Health and Quality of Life Outcomes)
Abstract Objective This study aims to translate and validate the CarerQol in a sample of informal caregivers in China. Method The CarerQol was translated following a standard process. Validation data was collected from multiple sources, including hospitals, patient associations, and community health centers between September 2023 and December 2024 in China. Caregivers of individuals with disability or long-term care needs were recruited. The psychometric properties of the CarerQol-7D were evaluated through ceiling and floor effects, factorial structure, convergent and divergent validity, known-groups validity, and test-retest reliability. Results A total of 324 participants completed the survey and provided validated responses. The mean CarerQol level sum score was 12.8 (SD = 2.9). The CarerQol-7D showed no ceiling or floor effects at either dimension or scale levels. Test-retest reliability of the CarerQol-7D was satisfactory, as supported by ICC and Gwet’s AC1 measures. Correlation analysis confirmed all hypothesized pairs of dimensions and level sum scores/utility scores between CarerQol-7D, SF-6Dv2, and ICECAP-A. The CarerQol-7D successfully distinguished between risk groups through ANOVA testing. Confirmatory factor analysis revealed that a one-factor model of the CarerQol-7D fit the data. Conclusion This study provides the Chinese version of the CarerQol and confirms its sound psychometric properties for informal caregivers in China. These findings demonstrate the CarerQol’s value in cost-effectiveness analyses of caregiving interventions and strategies.